THE EFFORTS OF TEACHERS OF THE AL-QUR'AN EDUCATION PARK OF THE AL-QUR'AN INTERPRETATION ASSEMBLY OF THE KEDAWUNG 4 BRANCH IN IMPROVING THE QUALITY OF NON-FORMAL ISLAMIC EDUCATION LEARNING - Putri, Hanifa Sahaja; Jinan, Mutohharun (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The purpose of this study is to discuss the efforts of teachers of the Kedawung 4 Branch Al-Qur'an Interpretation Assembly in improving the quality of non-formal learning. The type of research used is qualitative research with a case study research approach. This research data collection uses three techniques, namely observation, interviews, and documentation. The validity of this research data uses triangulation techniques. The data were then analyzed through data reduction, data presentation and conclusion drawing. The key in running education as educational empowerment is needed in improving the quality of reliable and professional teaching, qualified infrastructure, institutional quality and the efforts of teachers to carry out their profession. This study shows the efforts of TPQ teachers in learning as an effort to improve the quality of non-formal Islamic education. The steps used as teacher efforts, starting from creating creative learning ideas so as to foster learning motivation, educational activities to improve the quality of TPQ, and the training and coaching of TPQ teachers.